Characterizing pastoral land on a large scale : a way to assess better the resilience of Mediterranean livestock activities. Lessons learned from a study on the scale of the Provence Alpes Côte d’Azur region (France) - Shaqura I.; Lasseur J. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Given the mobility of people and animals, the diversity of land tenure systems and of the associated environments, the identification of grazing land over large areas is an uncertain exercise, especially when it comes to defining the expanse of land concerned and its type. Improving the characterization of grazing lands is needed to analyse the resilience of pasture-based systems in a context of global changes. Our study started with the determination of the diversity and spatial distribution of vegetation types within the grazing land of a small region, based on testimonies from livestock farmers. On this basis, we characterized land use by remote sensing at the scale of a small test region (611 km2). The characterization of land use in these areas is a major challenge that cannot be met merely by analysing declarative data or by using a conventional map where land categories cannot be connected to grazing management practices. On the basis the land use map we produced, we identified that animals’ access to the pastoral resource is problematic in a large proportion of the grazing area (35%) due to shrub encroachment and forest expansion. This puts forward a weakness of pastoral farming in terms of future dynamics.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)